Pseudohyperkalemia: Hyperkalemia Cocktail or Alternative Diagnosis - Sanjay Prakash Neupane; Pratibha Sharma; Mahesh Mani Dangal (Case Reports in Medicine)
Introduction. Hyperkalemia is a commonly encountered clinical problem. Pseudohyperkalemia is believed to be an in vitro phenomenon that does not reflect in vivo serum potassium and therefore should not be treated. Here, we present a case who unfortunately underwent unnecessary treatment because of failure to detect the common lab abnormality of pseudohyperkalemia. Case Presentation. A 91-year-old female with a history of chronic lymphocytic leukemia presented to the emergency with nausea and vomiting 24 hours after her first chemotherapy with chlorambucil. Physical examination was overall unremarkable. She had a leukocytosis of 210 × 103/µL with 96% lymphocytes along with chronic anemia with hemoglobin of 8.1 g/dL. Her initial sodium and potassium levels were normal. During the clinical course, her potassium progressively worsened and failed to improve despite standard medical treatment. Patient ultimately underwent dialysis. Conclusions. Differentiating true hyperkalemia from pseudohyperkalemia is very important in selected group of patients to avoid unnecessary medications, higher level of care, and unnecessary procedure including dialysis. We want to emphasize the importance of simple yet profound knowledge of technique of blood draws and basic metabolic panel processing for every clinician in day-to-day practice.